2018
DOI: 10.1155/2018/7041342
|View full text |Cite
|
Sign up to set email alerts
|

The Increase of Circulating PD-1- and PD-L1-Expressing Lymphocytes in Endometriosis: Correlation with Clinical and Laboratory Parameters

Abstract: The cause of endometriosis remains unknown. However, studies investigating the link between this condition and the immune system revealed several immunological abnormalities focused on cell-mediated immunity. As a major immune checkpoint, programmed cell death protein 1 (PD-1) displays an important inhibitory function in the maintenance of peripheral tolerance. The expression of PD-1 and its ligand (PD-L1) may contribute to continuous T cell activation and development of inflammation and injury of the tissue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 59 publications
0
27
1
1
Order By: Relevance
“…Considering the above immune regulatory functions of soluble immune checkpoint molecules, it seems that they play a crucial role in the pathogenesis of endometriosis. Recently, the membrane‐bound PD‐1/PD‐L1 expressed by lymphocytes and endometrial tissues were described in endometriosis 17‐19 . In the current study, we hypothesize that soluble immune checkpoint molecules in peripheral circulation and peritoneal fluid will be elevated during endometriosis in infertile women.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Considering the above immune regulatory functions of soluble immune checkpoint molecules, it seems that they play a crucial role in the pathogenesis of endometriosis. Recently, the membrane‐bound PD‐1/PD‐L1 expressed by lymphocytes and endometrial tissues were described in endometriosis 17‐19 . In the current study, we hypothesize that soluble immune checkpoint molecules in peripheral circulation and peritoneal fluid will be elevated during endometriosis in infertile women.…”
Section: Introductionmentioning
confidence: 64%
“…Previous studies have reported a systemic anti‐inflammatory state in endometriosis patients with elevated concentration of serum IL‐10, which is known as one of the effector molecules in immune checkpoint signaling pathway 22,23 . The significantly higher level of sCTLA‐4 and sPD‐L1 in the sera of advanced‐stage endometriosis might also be the outcome of increased proteolytic cleavage of membrane forms from the local endometrial‐like cell lesions, which then circulate into the periphery 17,18,20 …”
Section: Resultsmentioning
confidence: 98%
“…Hyporesponsiveness of T CD8+ cells may be contributing to their exhaustion [ 49 ]. In our previous research, we showed that advanced EMS was characterized by higher frequencies of programmed death-1 (PD-1)-positive T and B cells, which were the hallmark of T cell exhaustion [ 50 ]. Our results are interesting in light of a recently published study, in which CD200 overexpression on AML blasts suppressed CD4+ and CD8+ T lymphocyte function via the CD200/CD200R pathway.…”
Section: Discussionmentioning
confidence: 99%
“…88 Immunomodulatory factors may also be a result of lesion establishment, as suggested by greater numbers of circulating PD-1 þ T and B cells in advanced endometriosis. 89…”
Section: Genomic Regulation Of Cellular Pathways Involved In Endometrmentioning
confidence: 99%